Medical Cadets as Force Multipliers: Operational Readiness from the Sumatra Disaster Relief Task Force - Angki Perdiyana; AJ Didy Surachman (The ASEAN Journal of Military and Preventive Medicine, 2026)
Background: As an archipelagic territory highly vulnerable to severe weather anomalies, Indonesia requires prompt multi-sectoral deployment and flexible civil-military medical protocols to mitigate post-disaster health crises; hence, this study evaluates the operational integration, health service support, and health risks of military medical cadets serving in the Sumatra Disaster Relief Task Force. Methods: This study utilizing a descriptive field report with a narrative review component of disaster healthcare guidelines from 2016–2026, this research evaluated operational logbooks spanning November 30 to December 17, 2025. Results: The mission successfully achieved five strategic milestones, including logistical readiness, shipboard surgical assistance, management of an internal Typhoid Fever case, evacuation recovery, and multi-sectoral water purification installations. Frontline operations in Aceh Tamiang managed a high-throughput volume of 586 acute civilian cases over two days (n=305 on December 16; n=281 on December 17), where waterborne gastroenteritis, post-flood infectious dermopathy, and neglected chronic pathologies represented the primary clinical burden. Conclusion: Ultimately, deploying supervised senior military medical student volunteers functions as a vital mechanism to reinforce overloaded health infrastructures, though sustaining operational durability strictly depends on mandatory pre-deployment vaccinations, clear boundaries of practice, and rigid compliance with Incident Command Systems.